From shadow banking to digital financial inclusion: Regulatory framework contestation between China and the FSB - Peter Knaack; Julian Gruin (University of Oxford, Global Economic Governance Programme (GEG), 2017)
China's involvement in global financial regulatory governance in the wake of the global financial crisis has surprised many observers. While Beijing has pushed for governance reform in the international financial institutions and created alternative ones, Chinese representatives in the Financial Stability Board and the standard-setting bodies it coordinates have adopted a comparably passive stance. This paper however identifies recent signs of discontinuity in China's accepting embrace of global financial standards. While policymakers supported the interpretation of non-bank financial services as "shadow banking" early on, they are challenging this frame half a decade later. Global regulatory bodies are reluctant to adjust the frame of shadow banking in order to incorporate developing country preferences. In response, Chinese authorities are redefining the label of its fast-growing non-bank financial sector to imbue it with regulatory legitimacy. They have promoted a shift away from shadow banking to the overlapping frames of fintech (internet finance) and financial inclusion. The interaction between Chinese and international regulators reveals the options and constraints the rising power faces in the political economy of global financial regulatory governance.
Keywords: 330